The New Edition of the Tablature of Joannes de Lublin: Tradition and Perspectives - Kateryna Schöning (Muzyka)
The new edition of the tablature of Joannes de Lublin represents the state of the art in editorial practice, combining a critical and practical edition. It is discussed within the contexts of the contemporary corpus of  tablatures in Poland and also Central  European music, developing a series of current topoi: a new ordering and reconstructing of the material taking account of codicological research and functional purposes, the local reworking of the repertoire and compilatory practice of the scribes, unknown concordances or unica, counterpoint and intabulation techniques, syntactic-rhetorical properties, and historical didactics. The edition provides literal, but good, readable transcriptions.